BRYOFLORA TERESTRIAL DI ZONA TROPIK GUNUNG UNGARAN, JAWA TENGAH - Heti Ergiana; Erry Wiryani; Jumari J (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2013)
The Ungaran mount is a various kind area of biodiversity, either flora or fauna. One of the flora biodiversity there is bryoflora. Bryoflora are classified into two groups, terrestrial and epiphytic. The bryoflora researchs has been widely applied in the java island, but the related publication of terrestrial bryoflora in the Ungaran mount Central Java are rarely found. The purpose of the research is to explain the diversity of terrestrial bryoflora in the tropical zone (at altitude 750 m asl, 980 m asl, and 1100 m asl). The method for bryoflora sampling used quadrate with purposive sampling method. The result on this research in tropical zone of Ungaran mount found 50 spesies of bryoflora that were identified in to three division : Bryophyta, Marchantiophyta, and Anthocerophyta. The percentage of the Bryophyta that was found are: Bryophyta 56 % (34 species), Marchantiophyta 40 % (15 species), and Anthocerophyta 4 % (1 species). Based on the height of station were identified 26 species at altitude 750 m asl, 17 species at altitude 980 m asl, and 24 species at altitude 1100 m asl. Keywords: Terrestrial Bryoflora, Tropical Zone, Ungaran Mount